UPAYA PENERAPAN DIVERSI OLEH JAKSA TERHADAP ANAK BERKONFLIK DENGAN HUKUM DI TINGKAT PENUNTUTAN (STUDI DI KEJARI SERDANG BEDAGAI) - Sitinjak, Dicky Wirawan; Nadirah, Ida (JURNAL DOKTRIN REVIEW, 2023)
Criminal acts committed by children are a serious problem for the government in tackling criminal acts in Indonesia, where children are the perpetrators. As previously explained in the Indonesian constitution, the State guarantees every child's right to survival, growth and development and the right to protection from violence and discrimination, as explained in the 1945 Constitution Article 28 B paragraph 2. Because children are an important element of the State. The formulation of the problem is how to regulate diversion against ABH and how the Prosecutor's efforts to implement diversion against ABH, as well as what obstacles the Serdang Bedagai District Prosecutor's Office faces in efforts to implement diversion against ABH. Normative legal research methods. Regarding the provisions for diversion against ABH, it is regulated in Law No: 11 of 2012 UUSPPA, and efforts to implement diversion by Prosecutors against ABH, are regulated in PERJA No: PER-006/A/J.A/O4/2015 concerning Guidelines for Implementing Diversion in Prosecution Level, to respond to the mandate of the UUSPPA, in particular implementing the Prosecutor's obligation to seek diversion at the prosecution level. There are two types of obstacles found in implementing diversion, namely internal obstacles, namely special children's room facilities that do not meet standards and external obstacles that come from parties who are not willing to attend diversion deliberations. So the suggestion is that there should be an update in the UUSPPA because criminal acts committed by children are increasing, making ABH prevention regulations involving schools, parents and community leaders.